GAMBARAN LAKU SPIRITUAL KH. AHMAD BASYIR ABDULLAH SAJJAD - Muhammad Hadiyatullah (Living Sufism: Journal of Sufism and Psychotherapy, 2023)
The aspect of spirituality today is very crucial in supporting the orientation of human life in the future, which is basically being hit by an existential crisis. Thus, it is necessary to present a figure who can be a role model in dealing with this existential crisis problem, namely KH. Ahmad Basyir Abdullah Sajjad. This aims to be a guideline for humans, therefore, they are not trapped in a materialistic and hedonistic life. This research is a qualitative research with a transpersonal psychology approach carried out by Abraham Maslow, with a biographical narrative research method. From the results of this study, it is evident that KH. Ahmad Basyir Abdullah Sajjad is a perfect figure in implementing a figure who has a high level of spirituality as stated by Abraham Maslow.